Assessing Lung and Skin Cancer Risks for Steel and Iron Manufacturing Industry Workers Exposed to Polycyclic Aromatic Hydrocarbons - Ying-Fang Wang; Yu-Chieh Kuo; Ming-Yeng Lin; Perng-Jy Tsai (Aerosol and Air Quality Research)
Abstract Conducting both inhalatory and dermal samplings are crucial for chemicals, such as polycyclic aromatic hydrocarbons (PAHs), which are known with chronic dermal and inhalatory health effects. The present study is the first one set out for conducting both PAH inhalatory and dermal exposure assessments simultaneously for electric arc furnace (EAF) workers in an iron and steelmaking industry. The results were further used to assess the health risks posed on workers. Finally, risk-based control strategies were suggested. Three similar exposure groups (SEGs) of the melting, ladling, and casting were selected for conducting personal samplings. A total of 15 and 120 samples were collected for assessing workers’ inhalatory and dermal PAH exposures, respectively. Results show that the inhalatory gas-phase PAH exposure levels (2.17 × 104–1.52 × 105 ng m−3) were consistently higher than that of particle-phase (2.73 × 103–6.76 × 103 ng m−3) in all selected exposure groups. The mean inhalatory exposure concentrations of the melting and casting workers (2.84 × 104–3.32 × 104 ng m−3) were higher, but ladling workers (1.58 × 105 ng m−3) were lower, than the time-weighted average permissible exposure level (PEL-TWA) regulated in Taiwan (1.00 × 105 ng m−3). The estimated lifetime excessive lung cancer risks for the latter (2.09 × 10−3) were lower than that of the former (3.43 × 10-3–8.84 × 10−3), they were all higher than the significant risk (10−3) defined by the US Supreme Court. The mean whole-body total PAH dermal exposure levels were 2.84 × 105–7.45 × 105 ng day−1, and those body surfaces uncovered by clothes were found with higher exposure levels. Since the estimated lifetime excessive skin cancer risks (7.74 × 10−5–1.62 × 10−4) were lower than of the lung cancer risk, which indicates that the control of workers’ inhalatory exposures is more important than that of dermal exposures. The installation of effective ventilation systems and the use of proper personal respiratory protection equipment are recommended for the abatement of risks posed on workers associated with PAH exposures.